PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF DEVELOPING CREATIVE RELATIONAL THINKING IN STUDENTS (MMIT Proceedings, 2026)
This article examines the pedagogical conditions, psychological mechanisms and effective methods for developing creative relational thinking (creative and communicative thinking) in students studying in the higher education system. In a modern educational environment, the issues of forming students' skills not only for independent thinking, but also for active participation in collective creative processes are analyzed.
Keywords: creative relational thinking; creativity; divergent thinking; pedagogical technologies; interactive methods